Advancing e-commerce adoption among SMEs in Jordan: A path to digital transformation - Basim Abbas Ali Alobaydi; Mohammad Mahmoud Saleem Alzubi; Ali Mohammad Ali Alqudah (Heritage and Sustainable Development, 2025)
This research identifies how technological aspects help small and medium-sized businesses in Jordan develop their e-commerce activities. Critical technological elements investigated in this research consist of the ICT infrastructure, digital payment systems, cybersecurity, and technological literacy. Small and medium-sized enterprises must adopt e-commerce to thrive within the fast-evolving digital global marketplace. All significant factors assessed during this research showed that technological literacy stood out as the primary driver for e-commerce success by allowing SMEs to utilize digital tools efficiently. Digital payment systems establish reliable payment mechanisms for online purchases, which build consumer trust, while cybersecurity protects personal customer information and strengthens consumer trust. Jordanian SMEs struggle with digital transformation because they have limited ICT infrastructure alongside scarce transformative resources. The researchers gathered structured survey responses from 121 SMEs located throughout Jordan. All selected SMEs for this research had completed at least five years of business operation according to random selection criteria. SPSS served as the platform through which researchers surveyed relationships between technological aspects and e-commerce integration. Research outcomes deliver appropriate guidance for policymakers and business figures, enabling them to expand SME potential and accelerate e-commerce penetration in Jordan.